BIOCOMERCIO, FAIR TRADE AND ASSOCIATIVITY MODEL FOR PERUVIAN SUPERFOODS - Buse Thorne, Eduardo (2017)
Products known as "Superfoods" are currently in high demand in international markets. Peru has a great variety, among them, maca, quinoa, kiwicha and others, which have attracted interest in many markets because they are natural, organic, functional and nutraceutical products. Peru endorses them in order to promote the biocommerce of the "Superfoods Peru", combined with activities of organic certification, fair trade and associativity. They are fundamental parts for the development of companies formed by communities, that obtain economic benefits with improved quality of life for families and communities. PROMACA works with this model where it implements these organic agricultural practices, promotes specialization, fair trade, innovation and associativity among members, thus generating a greater benefit for those involved in the chain, for customers and the ecosystem.